Business schools and their contribution to society - Morsing, Mette; Sauquet Rovira, Alfons; Community of European Management Schools (Los Angeles ; London : SAGE, 2011)
This book explores the role of business schools through three key dimensions: how business school legitimacy has been challenged by the recent economic crisis and corporate scandals; how schools contribute to shaping and transforming business conduct and how institutions, past and present, develop their identities to face the challenges presented by the ongoing globalisation process.
"CEMS."
Includes bibliographical references and index.
rua 02/12/13
Loans
Keywords: Business schools -- Social aspects; Business education -- Social aspects; Social responsibility of business